2018
DOI: 10.3389/fmicb.2018.02266
|View full text |Cite
|
Sign up to set email alerts
|

Zika Virus Infection at Different Pregnancy Stages: Anatomopathological Findings, Target Cells and Viral Persistence in Placental Tissues

Abstract: Zika virus (ZIKV) infection in humans has been associated with congenital malformations and other neurological disorders, such as Guillain-Barré syndrome. The mechanism(s) of ZIKV intrauterine transmission, the cell types involved, the most vulnerable period of pregnancy for severe outcomes from infection and other physiopathological aspects are not completely elucidated. In this study, we analyzed placental samples obtained at the time of delivery from a group of 24 women diagnosed with ZIKV infection during … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
65
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 34 publications
9
65
0
Order By: Relevance
“…The majority of confirmed cases of ZIKV occurred in the second and third trimesters of gestation. However, when analyzing the trimester of ZIKV infection in children born with microcephaly, we noticed that most of them became infected in the first trimester of pregnancy, which is compatible with the literature, since pregnant women with infection in the first trimester have the most severe cases, as well as an increased risk of microcephaly in their conceptuses 11,12,13 .…”
supporting
confidence: 89%
“…The majority of confirmed cases of ZIKV occurred in the second and third trimesters of gestation. However, when analyzing the trimester of ZIKV infection in children born with microcephaly, we noticed that most of them became infected in the first trimester of pregnancy, which is compatible with the literature, since pregnant women with infection in the first trimester have the most severe cases, as well as an increased risk of microcephaly in their conceptuses 11,12,13 .…”
supporting
confidence: 89%
“…More severe damage to fetal development, such as microcephaly, has been shown when maternal ZIKV infection occurs in the first trimester of pregnancy (141). Histopathological findings in the placenta at this time were similar to those found in TORCH infections, including chronic villitis, edema, trophoblastic lesion, and an increase in HBCs (142). However, third semester placentas showed only delayed villous maturation without any pathological changes.…”
Section: Mechanisms Involved In Congenital Infectionsupporting
confidence: 74%
“…Finally, we show that atovaquone also works to inhibit ZIKV infection in human first-and second-trimester placental explants. Many studies have shown that placental cytotrophoblasts, trophoblasts, Hofbauer cells, and fibroblasts are susceptible to ZIKV (18,20,(70)(71)(72)(73)(74); thus, recreating the dynamics of this infection and host-virus interaction at the placental level makes this study relevant to the most vulnerable target of ZIKV, pregnant women.…”
Section: Discussionmentioning
confidence: 99%